(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Stunting in children under five is still a public health problem in Indonesia, including in Java and Bali Islands. One important factor that can influence the incidence of stunting is animal food consumption, which plays a role in fulfilling essential nutrients for growth. This study aimed to analyze the contribution of consumption of various types of animal food to the prevalence of stunting in children aged 0-59 months in Java and Bali Island. The study used an ecological design with secondary data from 122 districts/cities in six provinces in Java and Bali Islands (Banten, West Java, Central Java, DI Yogyakarta, East Java, and Bali). Data on stunting prevalence and animal food consumption in 2021 were analyzed using multiple linear regression. The average prevalence of stunting in the study areas was lower than the national average, but still categorized as a public health problem. Animal protein consumption has exceeded 100% of the Protein Adequacy Level in all provinces, with fish consumption being the highest. Regression results show that poultry meat consumption significantly contributes to reducing stunting prevalence (β=-0.346;p≤0.05), while fish consumption is positively associated with increasing stunting (β=0.168;p≤0.05). This is thought to be because fish consumption is dominated by processed or preserved fish products that have low nutritional quality.